Increased biocrust cover and activity in the highlands of Iceland after five growing seasons of experimental warming - Salazar, Alejandro; Gunnlaugsdóttir, Eyrún G.; Jónsdóttir, Ingibjörg S.; Klupar, Ian; Wandji, Ruth-Phoebe T.; Arnalds, Ólafur; Andrésson, Ólafur (Springer, 2024)
Aims: One of the most important questions of our time is how ecosystems will be transformed by climate change. Here, we used a five-year field experiment to investigate the effects of climate warming on the cover and function of a sub-Arctic alpine ecosystem in the highlands of Iceland dominated by biocrust, mosses and vascular plants. Methods: We used Open Top Chambers (OTCs) to simulate warming; standard surface and Normalised Difference Vegetation Index (NDVI) analyses to measure plant cover and function; gas analyzers to monitor biocrust respiration; and the Tea Bag Index approach to estimate mass loss, decomposition and soil carbon stabilization rates. Results: Contrary to our initial hypothesis of warming accelerating an ecological succession of plants growing on biocrust, we observed a warming-induced decreased abundance of vascular plants and mosses —possibly caused by high temperature summer peaks that resemble heat waves— and an increase in the cover of biocrust. The functional responses of biocrust to warming, including increased litter mass loss and respiration rates and a lower soil carbon stabilization rates, may suggest climate-driven depletion of soil nutrients in the future. Conclusion: It remains to be studied how the effects of warming on biocrusts from high northern regions could interact with other drivers of ecosystem change, such as grazing; and if in the long-term global change could favor the growth of vascular plants on biocrust in the highlands of Iceland and similar ecosystems. For the moment, our experiment points to a warming-induced increase in the cover and activity of biocrust. Peer reviewed